2019
DOI: 10.1111/jpm.12567
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural family intervention for people diagnosed with severe mental illness and their families: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Accessible Summary What is known on the subject? Cognitive behavioural therapy for psychosis (CBTp) and family intervention (FI) for psychosis are effective evidence‐based interventions, but they are practically difficult to be implemented in many clinical settings. The CBTp and FI approaches have been integrated to form cognitive behavioural family intervention (CBFI). This brief intervention may be more feasible to implement in clinical practice. A few individual studies reported the effectiveness of CBFI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…Results of the current study suggested that intervention focusing on reducing CC domains of EE might have a more significant benefit to change relapse outcomes. Two recent systematic reviews found cognitive behavioural family intervention and compassion-focused therapy may be beneficial to the schizophrenic patients and their families, in which both of the interventions target on the cognitive reappraisal and emotional resilience to foster a family climate and dynamic (Ma et al, 2020; Mui et al, 2019). These evidences confirmed the foci of family intervention with the purpose of reducing EE, specifically CC domains and enhancing the sense of warmth.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the current study suggested that intervention focusing on reducing CC domains of EE might have a more significant benefit to change relapse outcomes. Two recent systematic reviews found cognitive behavioural family intervention and compassion-focused therapy may be beneficial to the schizophrenic patients and their families, in which both of the interventions target on the cognitive reappraisal and emotional resilience to foster a family climate and dynamic (Ma et al, 2020; Mui et al, 2019). These evidences confirmed the foci of family intervention with the purpose of reducing EE, specifically CC domains and enhancing the sense of warmth.…”
Section: Discussionmentioning
confidence: 99%
“…It may be useful to factor in families (e.g. Habib et al, 2015;Ma et al, 2020;Nickels et al, 2016) and religion (Heffernan et al, 2016;Turner & Hodge, 2020) when designing psychosis self-help tools in the Nicaraguan and Latin American context. Future research could develop different versions of CBT-based self-help, and make a comparison of the effectiveness of these tools.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our findings suggest that reductions in patients’ severity of illness may alleviate FGs’ distress. Previous reviews conclude that Cognitive Behavioral Therapy for psychosis (CBTp), Family Interventions for psychosis (FIp) and Cognitive Behavioral Family Intervention (CBFI), which integrates CBTp and FIp, are effective reducing psychotic symptoms and slightly improving FGs’ mental health (Claxton, Onwumere, & Fornells‐Ambrojo, 2017; Ma et al., 2019). These interventions tend to modify or improve attitudes, insights or appraisal of treatment and caregiving in patients diagnosed with mental illness or their FGs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they share some components such as psychoeducation about the illness, emotion management, social and coping skills training, and communication with peers and healthcare providers (Claxton et al., 2017; Ma et al., 2019). However, these reviews failed to find a strong and persistent effect on reducing FGs’ distress (Claxton et al., 2017; Ma et al., 2019). A better understanding of FGs’ unmet needs and barriers to engagement in interventions should be clarified in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation